Evidence on the Relationships Between Total Fat Intake and Health Outcomes Other Than Unhealthy Weight Gain in Adults and Children: A Scoping Review - Marianne Visser; Sarah Gordon; Amanda Brand; Anel Schoonees; Celeste Naude (Cochrane Evidence Synthesis and Methods, 2026)
ABSTRACT Introduction Global guidance provides evidence‐informed recommendations on total fat intake to prevent unhealthy weight gain in adults and children, however, evidence regarding total fat intake and other health outcomes, particularly non‐communicable diseases (NCDs), also exists. This scoping review aimed to map and identify gaps in this body of evidence. Methods Four databases were searched from 2014 to 2024 for published systematic reviews (SRs), in any population, assessing the effects or associations of reduced total fat intake (e.g., ≤ 30% total energy [TE]), compared with usual fat intake (e.g., > 30%TE), on pre‐specified health outcomes other than measures of unhealthy weight gain or acute post‐prandial outcomes. We screened independently and in duplicate. Data were extracted, checked, and narratively summarized inductively by health topic. Results Sixty‐seven SRs were included. Eight were fully aligned (all included studies addressed the scoping review question) and reported on health topics related to NCDs, for example, cancers (gastrointestinal, hematological), bone and joint health, gastrointestinal and neurological disorders, and cardiometabolic outcomes. Fifty‐nine SRs partially addressed the scoping review question, reporting additional topics, for example, cancers (breast, gynecological, urological, liver, skin), and respiratory and liver disorders. Almost one third of included SRs ( n = 21) reported outcomes related to cardiometabolic risk and cardiovascular disease, obtained mostly from randomized controlled trial (RCT) evidence. Evidence for other topics was mostly observational. Overall, evidence was predominantly from high‐income countries, and in adults. Conclusions This scoping review maps available evidence on the relationships between total fat intake and health outcomes other than unhealthy weight gain and acute postprandial effects and demonstrated a heterogenous body of evidence, with several evidence gaps, predominantly relating to NCDs.